MGMT Expression Contributes to Temozolomide Resistance in H3K27M-Mutant Diffuse Midline Gliomas - Abe, Hideaki; Natsumeda, Manabu; Okada, Masayasu; Watanabe, Jun; Tsukamoto, Yoshihiro; Kanemaru, Yu; Yoshimura, Junichi; Oishi, Makoto; Hashizume, Rintaro; Kakita, Akiyoshi; Fujii, Yukihiko (Frontiers in Oncology, 2020)
Diffuse midline gliomas (DMGs) show resistance to many chemotherapeutic agents including temozolomide (TMZ). Histone gene mutations in DMGs trigger epigenetic changes including DNA hypomethylation, one of which is a frequent lack of O6-methyl-guanine-DNA methyltransferase (MGMT) promoter methylation, resulting in increased MGMT expression. We established the NGT16 cell line with HIST1H3B K27M and ACVR1 G328E gene mutations from a DMG patient and used this cell line and other DMG cell lines with H3F3A gene mutation (SF7761, SF8628, JHH-DIPG1) to analyze MGMT promoter methylation, MGMT protein expression, and response to TMZ. Three out of 4 DMG cell lines (NGT16, SF8628 and JHH-DIPG1) had unmethylated MGMT promoter, increased MGMT expression, and showed resistance to TMZ treatment. SF7761 cells with H3F3A gene mutation showed MGMT promoter methylation, lacked MGMT expression, and sensitivity to TMZ treatment. NGT16 line showed response to ALK2 inhibitor K02288 treatment in vitro. We confirmed in vitro that MGMT expression contributes to TMZ resistance in DMG cell lines. There is an urgent need to develop new strategies to treat TMZ-resistant DMGs.